Vector correlations in the O-2(a(g)(1), v=1) fragment formed in the 265 nm photodissociation of ozone - Hancock, G; Ritchie, G; Sharples, T (2013)
Angular momentum polarisation and translational anisotropy have been measured for the J = 17 and 18 rotational levels in the O(aΔ, v = 1) fragment formed from the photodissociation of ozone at 265 nm. The results show similarities to those previously measured for the most populated vibrational level, v = 0, produced from photolysis in the Hartley band. Translational anisotropy parameters are very similar for both fragments, consistent with prompt dissociation from a bent intermediate. Angular momentum alignment and orientation, however, are found to be consistently lower for J = 17, compared with J = 18, and the magnitude of the depolarisation is consistent with previous results obtained for the odd and even J fragments in v = 0, produced with the same speed at longer photolysis wavelengths. The results indicate a vibrational-state-independent mechanism for the difference in polarisation between even and odd rotational states observed at relatively low fragment speeds. © 2013 Copyright Taylor and Francis Group, LLC.